2009
DOI: 10.1016/j.jvs.2009.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Present and Future of Branched Stent Grafts in Thoraco-abdominal Aortic Aneurysm Repair: A Single-centre Experience

Abstract: Background and purpose: This study aimed to investigate the embolic potential of carotid plaques, employing both the presence and the rate of micro-embolic signals (MESs), based on the presence and timing (current or past) of symptoms, degree of stenosis and ultrasonic characteristics of plaques.Methods: We used the transcranial Doppler (TCD) to monitor MES and the Doppler ultrasound to classify carotid plaques in newly symptomatic (acute stroke or transient ischaemic attack (TIA)), formerly symptomatic (relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 0 publications
1
45
1
1
Order By: Relevance
“…Some centers have used branched devices exclusively while others have used fenestrations routinely. [16][17][18] Others utilize devices with a combination of branches and fenestrations. Published series have shown that fenestrations have an extremely high patency in the renal arteries while longer branches tend to kink over time as the aneurysm sac shrinks.…”
Section: N Discussionmentioning
confidence: 99%
“…Some centers have used branched devices exclusively while others have used fenestrations routinely. [16][17][18] Others utilize devices with a combination of branches and fenestrations. Published series have shown that fenestrations have an extremely high patency in the renal arteries while longer branches tend to kink over time as the aneurysm sac shrinks.…”
Section: N Discussionmentioning
confidence: 99%
“…2). Initial experiences with these devices have shown that total endovascular repair is effective and may reduce morbidity rates in patients with arch, thoracoabdominal, pararenal and juxtarenal aneurysms [14][15][16][17][18][19][20][21]. Treatment of chronic type B aortic dissection with the use of fenestrated devices has also been reported with good preliminary results [22,23].…”
Section: Fenestrated and Branched Stent Graftsmentioning
confidence: 99%
“…Parallel improvements in imaging technologies have allowed very precise preoperative planning of these custom-made endografts and a growing number of centers have reported their experience with endovascular repair of thoracoabdominal aortic aneurysms (TAAA) of all types using branched or fenestrated endografts. [5][6][7][8][9] Recent combined data from two centers in the United States and France described the experience of the endovascular treatment of 231 type IV TAAAs in patients deemed unfit for open surgery. 10 This study demonstrated a 30-day mortality of 2.6% with 2-year survival of 82%.…”
Section: Introductionmentioning
confidence: 99%